Correction: Do Not Go Gentle Into That Good Night - James B. Young (Methodist DeBakey Cardiovascular Journal)
This article details a correction to: Do Not Go Gentle Into That Good Night. MethodistDeBakey Cardiovasc J. 2022; 18(2): 111-113. doi: 10.14797/mdcvj.1079